Milk Profile and Association of Stage of Lactation with Milk Components in Malvi Cattle (Indian Journal of Animal Production and Management, 2024)
The present investigation was carried out to  investigate the milk composition, fatty acid profile,  vitamins, and antioxidants and association of stage  of lactation with milk components. For this study,  we collected 100 ml milk from 50 lactating Malvi  cattle at Livestock Research Station, Dag Jhalawar.  Jhalawar is situated in a humid region of Rajasthan.  Representative milk samples were collected and  brought to the laboratory. In the Analysis of  Variance, the statistical difference for TAC between  different stages of lactation was found significant  (p
Keywords: Milk composition; fatty acids; vitamins; antioxidant activity; Malvi cattle